Characterization of Liquid Smoke from Dried Water Hyacinth Using GCMS (Gas Chromatography-Mass Spectrophotometry) to Utilize Weeds as Food Preservative - Ratnani, R. D.; Hadiyanto, H.; Widiyanto, W.; Adhi, M. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Water hyacinth is a weed in Rawa Pening because of its rapid growth. A handling effort is a very crucial thing and must be done immediately. This study aims to characterize organic compounds in liquid smoke from dried water hyacinth. Characterization of organic compounds from dried water hyacinth was carried out on water hyacinth liquid smoke which was pyrolyzed at 200°C and 600°C. Pyrolysis times were run at 2 hours and 6 hours. Liquid smoke from dried water hyacinth was distilled before testing its chemical composition using GCMS brand Shimadzu type QP 2010S. The results of liquid smoke characterization are used to decide that liquid smoke can be utilized as a food preservative. The test results report that the liquid smoke produced had an acid percentage ranging from 29.63% to 37.23%, phenol from 1.04 to 6.11%, and the remaining carbonyl compounds from 55.99% to 68.90%. The highest component value was obtained at 600°C pyrolysis and 6 hours. The conclusion is that liquid smoke from dried water hyacinth can be used as a food preservative because it contains acid, phenol, and carbonyl and is free of Benzo (a) pyrene, which can cause cancer. So that the requirement for liquid smoke as a preservative can be achieved, whereas acid is a food preservative. This study generates the acquisition of natural food preservatives to utilize weeds. The research helps us utilize weeds to resist the Rawa Pening environment and manufacture food preservatives.